(untitled) (Nepal Journal of Environmental Science, 2024)
Noise pollution in the hospital area is a significant problem that may cause patients to respond negatively in several ways. This study assessed the existing noise condition in 14 hospitals by monitoring noise levels within the hospital compound and at the roadside of the respective hospital. The sound pressure level was measured in A-weighting sound level meters in the morning (8:00 AM -11:00 AM) and in the evening (3:00 PM- 6:00 PM) at 10 seconds of the time interval during the high traffic flow period on working days. The study revealed that the Equivalent Sound Pressure level (Leq) value exceeded 60 dBA, in the morning and the evening at both sites surpassing the standard prescribed by WHO, USEPA, and GoN standards. There was no difference in the measured noise level (Leq) in the morning and evening within the hospital compound at 95% confidence intervals. However, a significant difference was observed in the noise within the hospital compound and to the nearest road revealing that the compound wall within the hospital premises attenuates noise level. A survey conducted with 100 respondents revealed that 77% are aware of noise pollution and 79% identified vehicle noise as a major source of noise. The survey also revealed that they had health impacts due to traffic noise, 53% reported an increase in their temper, 45% reported sleep disturbances, 38% reported headaches, 36% complained of lacking concentration, 30% mentioned speech interference, and 6% complained of having chest pain. Hence the study shows that the patients in hospitals and people around are affected by noise pollution though the hospitals are declared as peace zones.